Transculturalizing Space in Arab Diasporic Poetry: A Spatial Study of Naomi Shihab Nye’s Poetry Collection Transfer - Mukattash, Eman K. (American & British Studies Annual, 2021)
In the aftermath of the spatial turn that started in the seventies of the previous century, much attention has been devoted to the representation of space in literary criticism. Prior to this, space either served as a background for the events in a literary work or was viewed within an extremely narrow scope which defined it as either central or peripheral. With such reductive readings, the need for a revolutionary critical approach to space in literary criticism has risen, not only in frequently read literary genres but in more recently developing ones. One case in point is Arab diasporic literature, in which space plays an integral role not only in shaping the diasporic relation to native and foreign lands, but in shaping the cross-cultural relations it engages in as well. In the poetry collection Transfer (2011) by the Palestinian-American author Naomi Shihab Nye, space is perceived beyond the physical reality of the native or the diasporic place which witnesses the interaction between the diasporic and the foreigner and is, therefore, transculturalized. As concluded from the analysis of a selection of the poems from Transfer, this transcultural space is marked a number of features. First, it cannot be defined geographically as central or peripheral, it cannot function outside a specific context, and it cannot be separated from the discourse of the text. In this sense, not only would adopting a spatial approach to Arab diasporic literature help deconstruct more traditional approaches to space, but it would also help address some of the most commonly raised questions in Arabic diasporic literature from a transcultural perspective.